2018
DOI: 10.1007/s00540-018-2547-z
|View full text |Cite
|
Sign up to set email alerts
|

Randomized comparative study between two different techniques of intercostobrachial nerve block together with brachial plexus block during superficialization of arteriovenous fistula

Abstract: ICBNB proximal approach provides a high success rate with less amount of rescue analgesia compared to the distal approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Thoracic wall blocks administered immediately superficial or deep to the serratus anterior muscle target the lateral cutaneous branches of thoracic spinal nerves [6][7][8]. Hence, serratus plane blocks performed at the second or adjacent rib can produce an intercostobrachial nerve blockade.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thoracic wall blocks administered immediately superficial or deep to the serratus anterior muscle target the lateral cutaneous branches of thoracic spinal nerves [6][7][8]. Hence, serratus plane blocks performed at the second or adjacent rib can produce an intercostobrachial nerve blockade.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, serratus plane blocks performed at the second or adjacent rib can produce an intercostobrachial nerve blockade. Indeed, Moustafa and Kandeel [8] showed that to block the intercostobrachial nerve, injecting between the pectoralis minor and serratus anterior muscles at the level of the third rib in the anterior axillary line provided a significantly higher success rate compared with subcutaneous injection along the medial side of the upper arm. Furthermore, ultrasound-guided local anesthetic infiltration in the proximity of the medial brachial cutaneous and intercostobrachial nerves on the surface of the latissimus dorsi muscle at the axilla has been reported with a success rate of 92.9% [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anesthetic coverage via a brachial plexus block alone is often inadequate, particularly when the surgical procedure extends into the proximal axilla. Although inclusion of an ICBN (T2) covers the T2 dermatomal distribution outside of the brachial plexus (C5-T1) [4,5], the ICBN performed subcutaneously may only achieve 50-90% adequate coverage with significant anatomic variability [6,7]. A high thoracic PVB can mitigate this weakness by supplying coverage of the necessary T1-2 dermatomes.…”
Section: Discussionmentioning
confidence: 99%
“…Because the ICBN originates from the T2 nerve root below the C5-T1 nerve roots comprising the brachial plexus, brachial plexus blocks are ideally supplemented with an ICBN infiltration block for medial, upper arm coverage [4,5]. Unfortunately, the ICBN block performed subcutaneously may only achieve 50-90% adequate coverage [6], likely stemming from significant anatomic variability [7].…”
Section: Introductionmentioning
confidence: 99%